Analysis of the Requirements of Knowledge Management Systems According to the Specification ISO 30401:2018 in the Oil Projects Company - Sarah Jabbar Saeed; Areej Saeed Khalil (Journal of Techniques)
This research aims to analyze the extent to which the requirements of knowledge management systems according to the specification ISO 30401:2018 in the Oil Projects Company. It includes measuring each of the following dimensions: organization context, leadership, planning, support, process, continuous improvement of the specification items. Where the research problem was diagnosed with a weakness in the knowledge of the researched company and its failure to manage it according to approved standards and systems, which negatively affects the employment of its knowledge stock in improving its products and services. A random sample of (170) employees from various administrative levels in the company was chosen. The checklist was used to collect information and adopt the Likert scale to measure the extent of the application of the dimensions of the specification and to diagnose the gap between the actual reality of the application with the requirements of ISO 30401:2018. The results of this research showed that the overall rate achieved by analyzing and measuring the availability of knowledge management systems requirements in accordance with ISO30401: 2018 in the company has obtained a percentage (53%) and an implementation rate (3), meaning that it is partially applied and fully documented, which led to a gap of (47%).